(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article provides information on migration processes and related sources, which are considered an important phenomenon in the millennia-long history of human society. Furthermore, when covering migrations (displacements) in the Central Asian region during the ancient and early medieval periods, as well as these processes in the region, reports will be presented on the analysis of written sources in Western (Greek, Roman) and Eastern (Armenian, Chinese, Arabic, and Persian) languages.